Rapid identification of early renal damage in asymptomatic hyperuricemia patients based on urine Raman spectroscopy and bioinformatics analysis - Kong, Xiaodong; Liang, Haoyue; An, Wei; Bai, Sheng; Miao, Yuyang; Qiang, Junlian; Wang, Haoyu; Zhou, Yuan; Zhang, Qiang (Frontiers in Chemistry, 2023)
Objective: It is very important and controversial when to start treatment in patients with hyperuricemia (HUA) without gout and chronic kidney disease (CKD). In this study, Raman spectroscopy technology was used to analyze urine samples, with key differentially expressed genes of CKD also screened based using bioinformatics. The biological functions and regulatory pathways of key expressed genes were preliminarily analyzed, and the relationship between them as well as the heterogeneity of urine components of HUA was provided. Methods: A physically examined population in 2021 was recruited as the research subject. There were 10 cases with normal blood uric acid level and 31 cases with asymptomatic HUA diagnosis. After collecting the general clinical data, data on the peak positions of urine were analyzed by Raman spectroscopy. An identification model was also established by using the multidimensional multivariate method of orthogonal partial least squares discriminant analysis (OPLS-DA) model to analyze the data by statistical methods, screen the key genes of CKD through the GEO database, and obtain the key biological peak positions to evaluate the renal function damage of CKD patients with HUA. Results: There were significant differences in the expression levels of uric acid (640 cm-1), urea, creatinine (1608, 1706 cm-1), proteins/amino acids (642, 828, 1556, 1585, 1587, 1596, 1603, 1615 cm-1) and ketone body (1643 cm-1) (P < 0.05). The top 10 differentially expressed genes were related to CKD (ALB, MYC, IL10, FOS, TOP2A, PLG, REN, FGA, CCNA2 and BUB1) were screened out. Compared with the differential peak positions analyzed by OPLS-DA model, it was found that the peak positions of glutathione, tryptophan and tyrosine may be involved in the establishment of CKD recognition model. Conclusion: The progression of CKD could be related to the expression of ALB, MYC, IL10, PLG, REN and FGA genes. Patients with HUA may have abnormal metabolism of glutathione, tryptophan, tyrosine and energy. The application of Raman spectroscopy to analyze urine samples and interpret the heterogeneity of the internal environment of asymptomatic HUA patients can be combined with the OPLS-DA model to mine the massive clinical and biochemical examination information on HUA patients.